Geochemical and Geological Characteristics of the Upper Ordovician–Lower Silurian Shales in the Upper Yangtze Basin, South China: Implication for the Shale Gas Exploration - Sun, Yuan-Yuan (ACS Omega, 2020)
[Image: see text] Shale gas exploration in the Upper Yangtze Basin has been conducted for over ten years. The successful drillings in the region suggest that well-planned geological survey and reservoir evaluation are indispensable for the success of these drillings. In this study, the shale gas potential of Late Ordovician to Early Silurian mudstones/shales of the Wufeng–Longmaxi formations in the Upper Yangtze Basin was evaluated. First, all of the available geochemical and petrological data from Late Ordovician to Early Silurian mudstones/shales in the region were compiled. Distributional patterns of total organic carbon (TOC) values, thickness, thermal maturity, and burial depth of organic-rich mudstones/shales from the targeted formations were then analyzed. Our results show that TOC values range from 1.20 to 5.12%; R(o) values range from 1.92 to 2.86%; porosity varies from 0.77 to 9.2%; permeability varies from 0.015 to 1.99 md; the composition of quartz group of mineral component ranges from 18 to 85%, 59% in average; and clay mineral component ranges from 7 to 56%, 31% in average. Finally, based on these comprehensive analysis, three areas with great potential, that is, Luzhou-Xishui, western Chongqing, and Wulong-Shizhu, were selected as targets for further shale gas exploration and exploitation.